2019
DOI: 10.1556/004.2019.001
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of four loci in Hungarian Yellow and broiler chickens

Abstract: Traditional selection has led to remarkable differences in allele frequencies among various chicken breeds. Indigenous and broiler-type chicken populations were genotyped for polymorphisms in thyroid hormone responsive Spot14α, prolactin (PRL), IGF-binding protein 2 (IGFBP2), and somatostatin (SST) genes in order to determine potential utilisation type-associated allele frequencies. Significant (P < 0.05) differences were detected between Hungarian Yellow and broiler populations for Spot14α, PRL, and IGFBP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…If the loss of muscle mass in human subjects is monitored, the proteolysis of IGFBPs can also represent a novel content of biomarker information. Our results may have implications for IGFBP-biomarker research in vertebrates [ 6 , 7 , 8 , 9 , 10 , 11 ] since circulating concentrations of IGFBP-2 or other IGFBPs may not as a rule be interpreted in only one direction and clearly have a sex-related physiological background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the loss of muscle mass in human subjects is monitored, the proteolysis of IGFBPs can also represent a novel content of biomarker information. Our results may have implications for IGFBP-biomarker research in vertebrates [ 6 , 7 , 8 , 9 , 10 , 11 ] since circulating concentrations of IGFBP-2 or other IGFBPs may not as a rule be interpreted in only one direction and clearly have a sex-related physiological background.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in Angus bulls and in conjunction with parameters of growth hormone secretion, concentrations of circulating intact IGFBP-2 were informative for the prediction of average daily weight gain [ 6 ]. On the genomic level, studies in pigs [ 7 , 8 ] and chicken [ 9 , 10 , 11 ] have identified single nucleotide polymorphisms of the gene encoding IGFBP-2 associated with altered growth and carcass weight, and the inclusion of the IGFBP-2 locus in selection programs has been discussed. The negative effect of IGFBP-2 on somatic growth seems evolutionary conserved and was provided in zebrafish characterized by a duplicated IGFBP-2 gene [ 12 ].…”
Section: Introductionmentioning
confidence: 99%